2018
DOI: 10.1021/jacs.7b13017
|View full text |Cite
|
Sign up to set email alerts
|

Macrocyclization of Interferon–Poly(α-amino acid) Conjugates Significantly Improves the Tumor Retention, Penetration, and Antitumor Efficacy

Abstract: Cyclization and polymer conjugation are two commonly used approaches for enhancing the pharmacological properties of protein drugs. However, cyclization of parental proteins often only affords a modest improvement in biochemical or cell-based in vitro assays. Moreover, very few studies have included a systematic pharmacological evaluation of cyclized protein-based therapeutics in live animals. On the other hand, polymer-conjugated proteins have longer circulation half-lives but usually show poor tumor penetrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 61 publications
(27 reference statements)
1
42
0
Order By: Relevance
“…In their subsequent work, it turned out that the cyclization of such an protein-poly(amino acid) conjugate yields particularly interesting protein-based therapeutics. 202 A G 3 -poly(amino acid)-SPh was conjugated to a cystein at the N-terminus of Cys-IFN-LPETG and this conjugate cyclized by SML. The macrocycle combines the advantages of polymer conjugation and cyclization of therapeutic proteins which was evident by greater stability, longer circulation half-life and higher tumor retention compared to the linear counterparts.…”
Section: Ligation Of Polymer Blocksmentioning
confidence: 99%
“…In their subsequent work, it turned out that the cyclization of such an protein-poly(amino acid) conjugate yields particularly interesting protein-based therapeutics. 202 A G 3 -poly(amino acid)-SPh was conjugated to a cystein at the N-terminus of Cys-IFN-LPETG and this conjugate cyclized by SML. The macrocycle combines the advantages of polymer conjugation and cyclization of therapeutic proteins which was evident by greater stability, longer circulation half-life and higher tumor retention compared to the linear counterparts.…”
Section: Ligation Of Polymer Blocksmentioning
confidence: 99%
“…2632 We envisage that the chemical modification of proteins by synthetic polypeptides, which we call PEPylation, could open up enormous possibilities. 3335 Particularly, the chemical diversity of synthetic polypeptides has been greatly expanded by incorporating noncanonical amino acids via ring-opening polymerization (ROP) of α-amino acid N -carboxyanhydrides (NCA) and utilizing d -amino acids. 20 Notably, during the preparation of this manuscript, Jiang et al reported the nonspecific grafting of zwitterionic polypeptides to uricase, 36 which showed extraordinarily low immunogenicity and outstanding safety profile in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…[73,74] They also found that head-to-tail macrocyclization of protein-P(OEG3-Glu)n conjugates enhanced the tumor retention, penetration, and antitumor efficacy of protein therapeutics. [71] Recent, our group synthesized an amphiphilic triblock copolymer methoxy poly(ethylene glycol)-block-poly(l-glutamic acid)block-poly-( -propargyl-L-glutamate) (mPEG-b-PLGA-b-PPLG). The PLGA block of mPEG-b-PLGA-b-PPLG was modified with dopamines containing catechol groups by amidation reaction, and the PPLG block was modified with a small tertiary-amine molecule by click reaction, generating a novel triblock copolymer, mPEG-b-PGCA-b-PGTA.…”
Section: Polypeptides-protein Conjugatesmentioning
confidence: 99%